2013
DOI: 10.1016/j.jprot.2012.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression profiles of human lymph and plasma mapped by 2D-DIGE and 1D SDS–PAGE coupled with nanoLC–ESI–MS/MS bottom-up proteomics

Abstract: In this study a proteomic approach was used to define the protein content of matched samples of afferent prenodal lymph and plasma derived from healthy volunteers. The analysis was performed using two analytical methodologies coupled with nanoliquid chromatography-tandem mass spectrometry: one-dimensional gel electrophoresis (1DEF nanoLC Orbitrap–ESI–MS/MS), and two-dimensional fluorescence difference-in-gel electrophoresis (2D-DIGE nanoLC–ESI–MS/MS). The 253 significantly identified proteins (p<0.05), obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 35 publications
(65 reference statements)
3
59
0
Order By: Relevance
“…Lymph fluid drained from the periphery via afferent lymphatic vessels bathes LNs with soluble foreign antigens as well as tissue-specific self-antigens and any other molecules present in the local periphery, such as cytokines from inflamed tissues or tumors (10). Because lymph originates as interstitial fluid surrounding the cells of peripheral tissues, it is enriched in peptides that are processed extracellularly, including those resulting from local catabolism, ECM degradation, apoptosis, and tissue remodeling (9,11). While tissue-resident DCs take up and process antigens for presentation on MHC molecules, often resulting in DC maturation and migration to LNs (12), free antigens can rapidly drain to the LN via the subcapsular sinus, where large antigens and opsonized material may be directly taken up by subcapsular macrophages (Figure 1).…”
Section: Transport and Trafficking Functions Of The Lymphatic Systemmentioning
confidence: 99%
“…Lymph fluid drained from the periphery via afferent lymphatic vessels bathes LNs with soluble foreign antigens as well as tissue-specific self-antigens and any other molecules present in the local periphery, such as cytokines from inflamed tissues or tumors (10). Because lymph originates as interstitial fluid surrounding the cells of peripheral tissues, it is enriched in peptides that are processed extracellularly, including those resulting from local catabolism, ECM degradation, apoptosis, and tissue remodeling (9,11). While tissue-resident DCs take up and process antigens for presentation on MHC molecules, often resulting in DC maturation and migration to LNs (12), free antigens can rapidly drain to the LN via the subcapsular sinus, where large antigens and opsonized material may be directly taken up by subcapsular macrophages (Figure 1).…”
Section: Transport and Trafficking Functions Of The Lymphatic Systemmentioning
confidence: 99%
“…Human afferent prenodal lymph samples were collected as described. 22 The lymph was centrifuged at 1500g for 10 minutes to remove all cellular components. All lymph samples were clear at the time of collection, and contaminating hemoglobin levels in samples were measured as less than 1% of that in whole blood.…”
Section: Gp38mentioning
confidence: 99%
“…40,41 Therefore, although our in vitro and in vivo analyses showed that MMPs are a major form of proteases in degrading core 1 O-glycan-deficient or desialylated PDPN, other proteases such as serine proteases, may also be involved in the regulation of PDPN levels. [42][43][44] PDPN induces platelet aggregation by interacting with CLEC-2 on platelets.…”
Section: Discussionmentioning
confidence: 87%